2021
DOI: 10.3389/fmed.2021.700982
|View full text |Cite
|
Sign up to set email alerts
|

Immunopathophysiology of Juvenile Spondyloarthritis (jSpA): The “Out of the Box” View on Epigenetics, Neuroendocrine Pathways and Role of the Macrophage Migration Inhibitory Factor (MIF)

Abstract: Juvenile spondyloarthritis (jSpA) is a an umbrella term for heterogeneous group of related seronegative inflammatory disorders sharing common symptoms. Although it mainly affects children and adolescents, it often remains active during adulthood. Genetic and environmental factors are involved in its occurrence, although the exact underlying immunopathophysiology remains incompletely elucidated. Accumulated evidence suggests that, in affected patients, subclinical gut inflammation caused by intestinal dysbiosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 204 publications
(206 reference statements)
0
6
0
Order By: Relevance
“…Juvenile spondyloarthritis (JSpA) encompasses chronic and heterogenous seronegative inflammatory disorders and is associated with the HLA-B27 genotype [ 98 , 99 ]. Compared to adults, JSpA has been associated with lower HLA-B27 positivity, less peripheral arthritis and enthesitis and instead has more hip arthritis, axial involvement and acute anterior uveitis [ 99 ].…”
Section: Nod-like Receptors In Juvenile Idiopathic Arthritis and Juve...mentioning
confidence: 99%
See 1 more Smart Citation
“…Juvenile spondyloarthritis (JSpA) encompasses chronic and heterogenous seronegative inflammatory disorders and is associated with the HLA-B27 genotype [ 98 , 99 ]. Compared to adults, JSpA has been associated with lower HLA-B27 positivity, less peripheral arthritis and enthesitis and instead has more hip arthritis, axial involvement and acute anterior uveitis [ 99 ].…”
Section: Nod-like Receptors In Juvenile Idiopathic Arthritis and Juve...mentioning
confidence: 99%
“…Compared to adults, JSpA has been associated with lower HLA-B27 positivity, less peripheral arthritis and enthesitis and instead has more hip arthritis, axial involvement and acute anterior uveitis [ 99 ]. Reduced expression of NLRP3 has been observed in JSpA and it is proposed that this contributes to permeability of the gut and subclinical inflammation which is seen in studies with defective NLRP3 inflammasome signaling (i.e., inflammatory bowel disease) [ 98 , 99 ]. On the other hand, it is important to note that a population study in Croatia found no association between a SNP in NLRP3 (Q705K) with JSpA or JIA [ 100 ].…”
Section: Nod-like Receptors In Juvenile Idiopathic Arthritis and Juve...mentioning
confidence: 99%
“…Data from animal models and studies of relatives of AS patients strongly suggest that these changes do indeed precede the onset of the disease [ 67 ]. In contrast to CRMO, where hyperactivation of the NLRP3 inflammasome and, thus, hyperproduction of IL-1β is thought to be the cause of bone inflammation, in AS, this hyperactivity was found to maintain gut homeostasis and thus protect against gut inflammation [ 68 ]. It appears that remodeling of the gut microbiota and increased induction of regulatory T cells are the main mechanisms responsible for the observed resistance [ 69 ].…”
Section: Links Between Crmo and Jspamentioning
confidence: 99%
“…There are also similarities in terms of treatment strategies. Indeed, both anti-TNF and anti-IL-17 have shown efficacy for these different diseases, which we could consider as an additional indirect argument in favor of a certain similarity [ 64 , 65 , 66 , 67 , 68 ]. It is possible, however, that TNF blockade interrupts inflammatory pathways in a nonspecific manner, whether or not the diseases have common pathophysiologic mechanisms.…”
Section: Links Between Crmo and Jspamentioning
confidence: 99%
“…Several studies have shown that IGU has good efficacy in rheumatic diseases and autoimmune diseases, such as improving RA, AS, systemic lupus erythematosus, IG4-RD, pulmonary interstitial disease, primary Sjögren's syndrome (PSS), etc. (Harjacek, 2021;Pu et al, 2021;Zeng et al, 2022a). In clinical practice, more and more rheumatologists use IGU to treat rheumatic and autoimmune diseases, but its efficacy and safety are still uncertain.…”
Section: Introductionmentioning
confidence: 99%